Development of Integrated Science Microlearning Learning Media with Lontara Bugis Local Wisdom Based on Responsive Website Design (RWD) - Teguh Putra Gusal; Sudarmin Sudarmin; Bambang Subali (Postgraduate, University of Mataram, 2023)
The research carried out has the aim of developing science microlearning learning media integrated with regional letters that is feasible, practical and effective. The development research (R&D) method was designed using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. The small-scale experiment was tested on 9 grade 8 students at SMPN 2 Marioriwawo and the large-scale experiment was implemented in the experimental group (8.2) of SMPN 2 Marioriwawo with 27 students. The research results in this study prove that the science microlearning learning media integrated with Lontara Bugis local wisdom based on Responsive Website Design (RWD) is very suitable for use in science learning. The practicality test based on teacher and student responses has very practical criteria. The effectiveness of the product was tested through an experimental method through a post-test only control group design research design. Hypothesis testing uses an independent sample t-test with significance results (2-tailed) = 0.01 < 0.05, which means that the learning outcomes of experimental class students are higher than the scores of control class students. The resulting responses from experimental class students were in the positive category. So the conclusion of this research is that the learning media products developed are feasible, practical and effective for use as media in the teaching and learning process (PBM).